Multiculturalism and Islamic Education: A Bibliometric Analysis of Scopus Publications 2015-2025 in Contribution to the SDGs - Zahratul Hana; Bunyamin Bunyamin (Maharot : Journal of Islamic Education, 2026)
The intersection of Islam and multiculturalism in education has generated a rapidly expanding yet fragmented body of literature across pesantren epistemology, curriculum policy, and migrant identity studies, but this literature has not yet been systematically mapped. This study addresses that gap by mapping the scholarly landscape of multicultural Islamic education through a bibliometric approach. Data were retrieved from Scopus through a PRISMA-guided selection process, resulting in 116 articles published between 2015 and 2025. The data were analyzed using VOS viewer and Biblioshiny, part of the Bibliometrix package in R. The findings show an annual growth rate of 27.48 percent, with a sharp increase after 2020, as well as a collaborative authorship pattern averaging 3.16 co-authors per document. Indonesia and Malaysia dominate the scholarly contributions, led by Universitas Islam Malang and Universiti Malaya, reflecting the sociopolitical urgency of managing religious diversity in multiethnic Muslim-majority societies. Keyword co-occurrence analysis identifies four clusters: pesantren-based education, tolerance and deradicalization, curriculum integration, and an emerging intersection with cultural-health discourse. The prejudice reduction dimension, especially tolerance and deradicalization, is more prominent than in global multicultural education literature, which tends to emphasize teacher competence and diversity awareness. Links to the Sustainable Development Goals, particularly SDG 4 and SDG 16, appear conceptually but remain marginal and implicit, rather than forming a mature research agenda. These findings contribute theoretically by refining Banks' multicultural education framework in Muslim-majority contexts and practically by guiding curriculum policymakers in designing teacher training on religious moderation.